4H leukodystrophy caused by a homozygous POLR3B mutation: Further delineation of the phenotype. Issue 7 (22nd April 2020) - Verberne, Eline A.; Dalen Meurs, Lotje; Wolf, Nicole I.; van Haelst, Mieke M.
Abstract: 4H leukodystrophy, also known as Pol III‐related leukodystrophy, is a rare autosomal recessive neurodegenerative disorder characterized by hypomyelination, hypodontia, and hypogonadotropic hypogonadism. It is caused by biallelic mutations in POLR3A, POL3RB, or POLR1C. So far, only two patients have been described with homozygosity for the common c.1568T>A (p.Val523Glu) POLR3B mutation, both of them showing a remarkably mild clinical course. Here, we report another patient with homozygosity for the same mutation, but with a more severe phenotype including ataxia, developmental delay, and intellectual disability. This information is of importance for clinicians to provide comprehensive counseling to patients with 4H leukodystrophy and their families.